Diagnostic Immunohistochemistry with Manual Tissue Microarray Technique: A Pilot Study on Non-Hodgkin Lymphoma - Gunasekaran, Kumudhini Priya; Kulandaivel, Anbu Lenin (Annals of Pathology and Laboratory Medicine, 2018)
BACKGROUND: Non Hodgkin lymphomas are clonal lymphoproliferative disorders that needs to be classified immunologically by variety of immunological markers targeted against specific antigens. Tissue microarray allows for high-throughput molecular profiling of tissue specimens using immunohistochemistry resulting in reduced consumption of time and reagents as compared to conventional immunohistochemistry. METHOD: This three-year single institutional observational study was conducted at Tirunelveli Medical College, Tirunelveli, Tamilnadu. 21 cases of histopathologically diagnosed NHL were subjected to Immunohistochemistry using manual Tissue microarray. Paraffin embedded tissue blocks of all the NHL cases formed donor blocks. Lay out for Tissue microarray was constructed followed by manual transfer of cored tissue from representative areas of donor blocks into recipient block using bone marrow needles. Immunohistochemistry was done using antibody against CD3, CD5, CD10 and CD20. Inadequate lymph node samples, poorly processed samples and extranodal NHL were excluded. RESULT: Of total 21 cases subjected to immunohistochemistry using Tissue microarray technique, only 19 cases were taken for analysis due to tissue loss and histopathological misdiagnosis. Among 19 cases there were 11[57.89%] males and 8[42.11%] females with male to female ratio of 1.37:1. Mean age of study group was 54.7 years. There were 18[94.73%] cases of B-cell NHL with 1[5.27%] case of T-cell NHL. DLBCL constituted for 9[47.36%] cases. Immunohistochemistry using Tissue microarray consumed 1/6th of the reagent volume as that of conventional immunohistochemistry.